Delay-Independent Stability of Switched Linear Systems with Unbounded Time-Varying Delays. (6th June 2012) - Sun, Yuangong
Abstract : This paper is focused on delay-independent stability analysis for a class of switched linear systems with time-varying delays that can be unbounded. When the switched system is not necessarily positive, we first establish a delay-independent stability criterion under arbitrary switching signal by using a new method that is different from the methods to positive systems in the literature. We also apply this method to a class of time-varying switched linear systems with mixed delays.